Model-based evaluation of management options in ornamental plant nurseries. (20th October 2020) - Ruett, Marius; Whitney, Cory; Luedeling, Eike
Abstract: Agricultural management decisions are usually made without perfect knowledge. Decision Analysis (DA) approaches translate available uncertain information on costs, benefits and risks involved in decisions into actionable management recommendations. We illustrate the use of DA procedures to inform decisions on disease management strategies in ornamental plant production. We worked with heather growers and other stakeholders in North Rhine-Westphalia, Germany, to model the impacts of changing disease management practices and to generate comprehensive forecasts of net returns. Through sensitivity analysis and Value of Information assessment we identified critical uncertainties regarding the feasibility of improved practices. Partial Farm Budgets for decision options ranged from a loss of more than 200, 000 € to a gain of nearly 70, 000 € per hectare and year. Findings suggest that reducing pesticide applications without additional monitoring may substantially increase production risks (chance of loss of 76%) and that intensified plant monitoring is likely to increase net benefits (chance of gain of 68%) by allowing earlier detection and more focused fungicide application. Our Decision Analysis approach facilitated ex-ante evaluation of innovative management strategies in heather production, and it holds promise for similar evaluations in other agricultural production systems. Graphical abstract: Image 1 Highlights: Complex horticultural production systems often lack formal decision support. Decision Analysis enables forecasting management outcomes for disease management. Increased monitoring has higher net benefits than established management. Uncertainty on disease prevalence makes reduced spraying a risky strategy. Monitoring cannot compensate negative impacts of reduced preventive spraying.